2019
DOI: 10.1074/jbc.ra119.010298
|View full text |Cite|
|
Sign up to set email alerts
|

The ACT domain in chloroplast precursor–phosphorylating STY kinases binds metabolites and allosterically regulates kinase activity

Abstract: Protein import of nucleus-encoded proteins into plant chloroplasts is a highly regulated process, requiring fine-tuning mechanisms especially during chloroplast differentiation. One way of altering import efficiency is phosphorylation of chloroplast transit peptides in the cytosol. We recently investigated the role of three serine/threonine/tyrosine (STY) kinases, STY8, STY17, and STY46, in precursor phosphorylation. These three kinases have a high degree of similarity and harbor a conserved aspartate kinase–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…(6) Transport processes across the inner membrane of the chloroplast envelope are adjusted in response to low temperatures (Guan et al ., 2019; Trentmann et al ., 2020). (7) Fine‐tuning of chloroplast protein import contributes to effective plant development and acclimation (Lamberti et al ., 2011; Eisa et al ., 2019a; Eisa et al ., 2019b).…”
Section: Ra2 Metabolism: Metabolic Changes That Promote Acclimation mentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Transport processes across the inner membrane of the chloroplast envelope are adjusted in response to low temperatures (Guan et al ., 2019; Trentmann et al ., 2020). (7) Fine‐tuning of chloroplast protein import contributes to effective plant development and acclimation (Lamberti et al ., 2011; Eisa et al ., 2019a; Eisa et al ., 2019b).…”
Section: Ra2 Metabolism: Metabolic Changes That Promote Acclimation mentioning
confidence: 99%
“…The efficiency of protein uptake is influenced by phosphorylation of the precursor proteins, mediated by the cytosolic protein kinases STY8, 17 and 46 (Lamberti et al ., 2011). Our consortium recently showed that S ‐adenosyl methionine and isoleucine – both of which are synthesised in the chloroplast – bind to the highly conserved STY‐specific aspartate kinase–chorismate mutase–tyrA domain, which leads to the inhibition of kinase activity (Eisa et al ., 2019a). In addition, rates of precursor protein import are reduced under high light conditions owing to a decrease in the expression of the STY kinase genes (Eisa et al ., 2019b).…”
Section: Ra2 Metabolism: Metabolic Changes That Promote Acclimation mentioning
confidence: 99%
“…Finally, when a stress stimulus arrives, there is only a short window of time to modify and import nuclear-encoded proteins into the chloroplast before the gate closes. Protein phosphorylation is a very fast reaction occurring on a time scale of seconds to minutes, which has been observed in the regulation of TOC import capacity and of SSU import into the chloroplast [ 77 , 78 , 79 , 80 , 81 ]. Indeed, Serine/threonine/tyrosine (STY) protein kinases have been proposed to phosphorylate the SSU CTP to regulate the import of the related pre-protein [ 67 ].…”
Section: Chloroplastic Import: a Dynamic Gatekeeper Of Coordination?mentioning
confidence: 99%
“…The coding regions for STY8, STY46, and STY17 were cloned in the expression vector pET21a + with a C-terminal His-tag (Novagen) and purified as described previously [8]. pOE23, pHCF101, pNdhM, and pFNRL1 were cloned in the expression vector pET21a + with the following primers introducing appropriate restriction sites: pOE23_SacI_fr 5 -AGTCGAGCTCATGGCGTACAGTG CGTGT-3 , pOE23_NotI_rev 5 -CCCACCGCGGCCGCAGCAACACTGAAAGAAGT-3 , pHCF101_ SacI_fr 5 -ACTCGAGCTCATGCCGCTTCTTCATCCACA-3 , pHCF101_NotI_rev 5 -CCCACCGCG GCCGCGACTTCGACTGGAGACAA-3 , pNdhM_SacI_fr 5 -AGTGAGCTCATGGTTGCAGCATTC-3 , pNdhM_NotI_rev 5 -TGCTTAGCGGCCGCAGCGTCCTCTTGAGG-3 , pFNRL1_SacI_fr 5 -AGTC GAGCTCATGGCTGCTGCTATA-3 , pFNRL1_SacI_rev 5 -CCCACCGCGGCCGCGTAGACTTCAA CATT-3 .…”
Section: Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…Identification of the responsible dual specificity kinases STY8, STY17, and STY46 provided a tool to investigate the impact of preprotein phosphorylation in vivo, revealing that their impairment results in delayed chloroplast biogenesis [6,7]. Moreover, we recently showed that the kinases are regulated metabolically via an ACT domain [8].…”
Section: Introductionmentioning
confidence: 99%